2021
DOI: 10.1186/s13034-021-00371-9
|View full text |Cite
|
Sign up to set email alerts
|

Elementary school teachers knowledge and attitude towards attention deficit-hyperactivity disorder in Gondar, Ethiopia: a multi-institutional study

Abstract: Background A child suffering from attention deficit hyperactivity disorder (ADHD) faces many difficulties in social as well as academic performances. School teachers’ knowledge and attitude towards ADHD play a vital role in early detection and referral of the child to treatment centers. Few existing reports, however, indicate the alarming rate at which the problem is highly neglected in sub-Saharan Africa. The present study is designed to determine the knowledge, attitude, and factors that affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…This finding reveals that these are the main sources for parents to acquire knowledge on ADHD. Comparable results were reported by Dodangi et al (2017), Alshehri et al (2020), andDessie et al (2021). This suggests that the publicity and popularization of basic knowledge on ADHD should be increased through mass media, and medical staff should increase the popularization of ADHD knowledge to improve parental awareness of ADHD.…”
Section: Discussionmentioning
confidence: 75%
“…This finding reveals that these are the main sources for parents to acquire knowledge on ADHD. Comparable results were reported by Dodangi et al (2017), Alshehri et al (2020), andDessie et al (2021). This suggests that the publicity and popularization of basic knowledge on ADHD should be increased through mass media, and medical staff should increase the popularization of ADHD knowledge to improve parental awareness of ADHD.…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, a study in northern Jordan reported higher knowledge about ADHD general features followed by symptoms and diagnosis subclass than ADHD treatment with a mean total knowledge of 21.3% (30). Surprisingly a study conducted in Ethiopia stated that teachers had higher knowledge about ADHD treatment than the rest of the subclasses (31).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Dessie et al (2021) used the attitudes section, the Scale for ADHD Specific Attitudes, of the aforementioned research instrument ( Mulholland, 2016 ), to assess the ADHD-specific attitudes of 636 in-service teachers in Gondar, Ethiopia. They found that 84.1% of teachers held favorable attitudes toward ADHD and that the likelihood of reporting favorable attitudes were 1.85 times higher when the teachers had previous experience teaching a child with ADHD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only a handful of studies investigated the influence of other socio-demographic features on ADHD-specific attitudes. Results suggested that teaching students with ADHD diagnoses increased positive attitudes toward them ( Amha & Azale, 2022 ; Dessie et al, 2021 ), as did watching mass media as an information source about ADHD (Dessie et al). Furthermore, Cueli et al (2022) found that as teachers aged, their ADHD-specific attitudes became more negative, while having a close relationship with a student who had ADHD, having a relative with ADHD, or having ADHD themselves led to more positive opinions of their students with ADHD ( Flavian & Uziely, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%